Preface - Franca Daniele (European Scientific Journal, ESJ, 2022)
This Special Edition of the European Scientific Journal (ESJ) results from the speeches that were held on 26-28 October, 2021 at the online 9th Mediterranean Interdisciplinary Forum on Social Sciences and Humanities Multidisciplinary Conference. The Conference had several Special Sessions and I had the honor to chair the session on English for Specific Purposes.